Effect of Connector on Smoke Temperature with Function of Pressing Capsules. Issue 1 (April 2020) - Wang, Hao; Yu, Zhenhua; Zheng, Han; Zhan, Jianbo; Li, Geng; Zhang, Ying; Xie, Jiao; Wang, Xu; Yu, Tingting; Yue, Baoshan; Wang, Tao; Yu, Jiang; et al.
Abstract: In order to solve the shortcomings of single, fixed and irreplaceable cigarette capsules, the design of connector with function of pressing capsules which can replace and extrude multiple capsules at the same time was carried out, and the influence of this connector on smoke temperature was studied. ISO smoking model was applied to simulate the smoking process, and ANSYS software was used to fit the measured smoke. The geometric models of the smoke channel and the filter were established and meshed respectively. The pressure drop and temperature variation of the connector and the filter were simulated. The simulation results showed that CO and nicotine temperature were in transit. After passing the connector, the temperature drops sharply. When the filter rod reaches room temperature, it proves that the connector achieves the effect of reducing the smoke temperature.